PENGARUH BEBAN, KEPUASAN, DAN STRESS KERJA TERHADAP MOTIVASI KERJA PERAWAT: (A SYSTEMATIC REVIEW) - Yusuf Hanafi Lubis; Fennisyah Andriani Saragih; Betty Maretta (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
The Indonesian National Nurses Union (PPNI) (2011) revealed that as many as 50.9% of Indonesian nurses who work experience work stress, often feel dizzy, tired, less friendly, lack of rest due to excessively high workload and inadequate income. The objectives of the study was to look at the effect of workload, work stress, job satisfaction on work motivation on nurses: a systematic review. The research method used is systematic review to synthesize research results that are qualitative descriptive, with meta synthesis. The results of the study obtained a value of thitung X2 of 11,494 > 1,993 or α = 0.05, where sig = 0.000. In accordance with the hypothesis testing criteria that H0 is rejected and H3 is accepted, it means that the workload variable has a partially significant effect. There is a partial effect of work stress on the performance of nurses in Bali Provincial Hospital namely Pyx2 = - 0.533 with a p-value of 0.000 smaller than alpha (α) = 0.05. Ability (X1) has a significant influence on patient care (Y) when the nurse's work motivation (X2) remains (t calculated ≥ than the table t, 13,305 ≥ than in 1,907. In conclusion, the burden, satisfaction, and stress of work simultaneously have a significant effect for on the motivation of the nurse's work variable. Advice for agencies, to provide adequate rest time, as well as a reduction in shift hours to nurses so that there is no stress at work.